2017
DOI: 10.1007/s40005-017-0365-1
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical and pharmacokinetic evaluation of novel rectal mucoadhesive hydrogels containing tolmetin sodium

Abstract: The objective of the present study was to develop rectal mucoadhesive hydrogels loaded with Tolmetin Sodium, a nonsteroidal anti-inflammatory drug, for prolonged duration of action and increased bioavailability. Fourteen formulae were prepared with different types and concentrations of polymers as hydroxypropylmethyl cellulose, hydroxylethyl cellulose, carboxymethyl cellulose and sodium alginate. Each formulation contain Tolmetin Sodium equivalent to 5% w/w active drug. The effect of the employed gel bases on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 14 publications
(17 reference statements)
1
31
0
Order By: Relevance
“…A variety of nano‐sized drug delivery systems (DDS) have been designed to increase the bioavailability of antitumor drugs, improve drug delivery efficiency to specific sites, and enhance antitumor efficacy of drugs . Resesarch interests have been focused on the development of pH‐responsive drug carriers, taking advantage of the weak acidity characteristic (ie, pH 6.5‐7.0) outside the tumor cells and the endosomal/lysosomal acidic pH characteristic inside the tumor cells .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of nano‐sized drug delivery systems (DDS) have been designed to increase the bioavailability of antitumor drugs, improve drug delivery efficiency to specific sites, and enhance antitumor efficacy of drugs . Resesarch interests have been focused on the development of pH‐responsive drug carriers, taking advantage of the weak acidity characteristic (ie, pH 6.5‐7.0) outside the tumor cells and the endosomal/lysosomal acidic pH characteristic inside the tumor cells .…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, polysaccharidic drug carriers are most suitable for this purpose, and functional groups rich in biodegradable/biocompatible polysaccharides can be also utilized for next generation DDS applications . Agreeing with this situation, if novel types of chemotherapeutic drug carriers are developed through a chemical modification strategy of polysaccharides, it is likely to provide a transition period for chemotherapy …”
Section: Introductionmentioning
confidence: 99%
“…Following these standards, different injectable hydrogels protocols were developed and optimized, which because the body very well tolerated them, are ideal candidates for performing in vivo testing on rodents [176]. Given the fact that these delivery systems are suitable for clinical use, the most accessible routes of administration are subcutaneous [177], oral [178], rectal [179], topical and transdermal [180], orthotopic [181], intraperitoneal [182] and ocular [183]. Figure 3 represents all these administration routes.…”
Section: Hydrogel Administrationmentioning
confidence: 99%
“…Based on an earlier study that showed excellent biocompatibility on the digestive tract [195], rectally administrated catechol-chitosan- based hydrogels with mucoadhesive properties have been tested in murine models and show no toxic effects after 10 days [196]. Regarding this issue, Afaf A. et al, developed a hydrogel-based product and made a correlation between in vitro and in vivo profile with promising results [179].…”
Section: Hydrogel Administrationmentioning
confidence: 99%
“…The drug content was quantified by dispersing 1 g gel in 25 ml of methanol and centrifuged at 15000 rpm at 4 °C for 30 min. The analysis was done in triplicate and the percentage drug content was calculated [37].…”
Section: Drug Contentmentioning
confidence: 99%